Effective Taxation Modeling Based on International Experience - Zhovnir, Nataly; Shevchenko, Olena; Halai, Vasyl; Kyslytsia, Svitlana (International Journal of Engineering and Technology, 2018)
Foreign experience in taxation has been generalized in the article based on the analysis of Ukrainian fiscal system. Modern approaches in direct and indirect profit and consumption taxation have been determined. Effective taxation methodology based on the taxation burden management modeling has been proposed.Â Â Â